Specific character improvement - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1983)
Research carried out by CIAT on specific character improvement is described and the results obtained in the following studies are given: resistance to viral (BCMV, combined BCMV and BYMV, bean chlorotic mottle virus, and BGMV), fungal (anthracnose, angular leaf spot, rust, and web blight), and bacterial diseases (halo blight and common bacterial blight), and to pests (Empoasca kraemeri, Zabrotes subfasciatus, Acanthoscelides obtectus, and Apion godmani); yield and plant architecture improvement; material selection for tolerance to moderately acid soils and to water stress, and for potential for N fixation; variability from interspecific hybridization. Several special studies were carried out on heterosis, hybrid dwarfism, and starch accumulation in stems and roots. (CIAT)